The Influence of Business Locations on Sales Volume - Dhea Paramitha (SEAN Institute, 2022)
This study aims to find out the Factors That Affect the Sales Volume of Traders in Tanjung Morawa Market. The samples used in this study were Tanjung Morawa Market Traders, aged 17 years or older, and were traders who owned businesses in tanjung morawa market. The number of samples is calculated using the formula slovin then obtained the number of samples as many as 244 people. The results of this study showed that free variables, namely Business Location, have a positive and significant effect on the Sales Volume of Tanjung Morawa market traders.